AB0133 HUMAN UMBILICAL CORD-DERIVED MESENCHYMAL STEM CELLS AMELIORATE COLLAGEN-INDUCED ARTHRITIS VIA IMMUNOMODULATORY EFFECT ON T LYMPHOCYTES. (June 2019) - Ma, Dan; Xu, Ke; Zhang, Gailian; Liu, Yang; Gao, Jinfang; Tian, Min; Wei, Chun; Juan, LI; Zhang, Liyun
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune disease that results in cartilage and bone destruction. Overactivation of T lymphocytes and imbalance of T lymphocyte subsets are closely related to the occurrence and development of RA. These have become important mechanisms of inflammation, immune activation, and bone destruction. RA treatment ideally involves regulation of immune abnormalities and maintenance of immune homeostasis. Mesenchymal stem cells (MSCs) are multipotent adult stem cells with high proliferation, multi-differentiation, and immune regulation. They exert immunoregulatory effects on T lymphocytes to improve RA symptoms, inhibit synovial hyperplasia, and reduce cartilage and bone erosion. However, the specific molecular mechanisms have not been fully elucidated. Objectives: This study investigated the effect of human umbilical cord mesenchymal stem cells (hUCMSCs) on collagen-induced arthritis (CIA) in rats in comparison with that of methotrexate (MTX), a classical drug for RA. It evaluated T lymphocyte proliferation, apoptosis, differentiation, and associated inflammatory factors, futher explored the regulatory mechanism of T lymphocyte differentiation at the gene transcription level. This study elucidated that hUCMSCs play an immunoregulatory role in T lymphocytes of CIA rats through multiple pathways and explored the possible mechanism of hUCMSCs in RA treatment via the immunomodulated T lymphocyte pathway. Methods: The effects of hUCMSCs on arthritis, radiological and synovial pathological changes in CIA rats were assessed. Flow cytometry was conducted to detect T lymphocyte proliferation, apoptosis, the ratio of Th17 and Treg cells in the spleen, and IL-17 and TGF-β levels in the sera from CIA rats. Further, Foxp3 and ROR-γT expression in the spleen were assessed by immunohistochemistry, Foxp3mRNA and ROR-γTmRNA expression were assessed by reverse transcription-polymerase chain reaction (RT-PCR). Results: hUCMSCs inhibited proliferation and promoted apoptosis of T lymphocytes, up-regulated Foxp3 mRNA and protein expression, increased the proportion of Treg cells, down-regulated ROR-γT mRNA and protein expression, and decreased the proportion of Th17 cells in the spleens of CIA rats. Correction of the Foxp3/ROR-γT imbalance to regulate the Treg/Th17 ratio, promoted anti-inflammatory factor TGF-β expression and inhibited pro-inflammatory factor IL-17 expression, thereby improving arthritis in CIA rats, delaying radiological progression, and inhibiting synovial hyperplasia. This effect was similar to that of MTX. Conclusion: hUCMSCs exert immunoregulatory effects on T lymphocytes in CIA rats through many pathways and are expected to become a new immunoregulatory therapy for RA. References: [1] KONDO Y, YOKOSAWA M, KANEKO S, et al.: Review: Transcriptional Regulation of CD4+ T Cell Differentiation in Experimentally Induced Arthritis and Rheumatoid Arthritis. Arthritis Rheumatol 2018; 70: 653-61. [2] ANSBORO S, ROELOFS AJ, DE BARI C: Mesenchymal stem cells for the management of rheumatoid arthritis: immune modulation, repair or both?. Current Opinion in Rheumatology2017; 29: 201-7. [3] SUN Y KW, HUANG S, SHI B, et al.: Comparable therapeutic potential of umbilical cord mesenchymal stem cells in collagen-induced arthritis to TNF inhibitor or anti-CD20 treatment. Clin Exp Rheumatol2017; 35: 288-95. [4] PARK KH, MUN CH, KANG MI, LEE SW, LEE SK, PARK YB: Treatment of Collagen-Induced Arthritis Using Immune Modulatory Properties of Human Mesenchymal Stem Cells. Cell Transplant2016; 25: 1057-72. [5] YANG Y, HU X, CHENG L, et al.: Periplocoside A ameliorated type II collagen-induced arthritis in mice via regulation of the balance of Th17/Treg cells. Int Immunopharmacol2017; 44: 43-52. Disclosure of Interests: None declared